2014
DOI: 10.1186/1752-0509-8-s1-s4
|View full text |Cite
|
Sign up to set email alerts
|

Genes associated with genotype-specific DNA methylation in squamous cell carcinoma as candidate drug targets

Abstract: BackgroundAberrant DNA methylation is often associated with cancers. Thus, screening genes with cancer-associated aberrant DNA methylation is a useful method to identify candidate cancer-causing genes. Aberrant DNA methylation is also genotype dependent. Thus, the selection of genes with genotype-specific aberrant DNA methylation in cancers is potentially important for tailor-made medicine. The selected genes are important candidate drug targets.ResultsThe recently proposed principal component analysis based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The NUAK1 gene (NUAK Family, SNF1‐Like Kinase, 1), which codes for protein kinase, is involved in processes such as cell adhesion, cell proliferation and senescence. NUAK1 is overexpressed in many human cancers, including squamous cell carcinoma (SCC) . It has also been implicated in tumour invasion and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…The NUAK1 gene (NUAK Family, SNF1‐Like Kinase, 1), which codes for protein kinase, is involved in processes such as cell adhesion, cell proliferation and senescence. NUAK1 is overexpressed in many human cancers, including squamous cell carcinoma (SCC) . It has also been implicated in tumour invasion and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Although PCA based unsupervised FE was applied to various bioinformatics problems [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], we briefly describe the outline of this methodology. Let x ij be the expression of the ith mRNA/miRNA of the jth sample, and suppose that .…”
Section: Pca Based Unsupervised Fementioning
confidence: 99%
“…The various unsupervised gene selection methods were invented, e.g., highly variable genes, bimodal genes and dpFeature and principal component analysis (PCA) based unsupervised feature extraction (FE) (50, 34, 49, 42, 25, 31, 27, 40, 47, 4, 5, 44, 45, 13, 12, 11, 51, 39, 43, 22, 23, 24, 26, 41, 48). Chen et al (2) recently compared genes selected by these methods and concluded that the genes selected are very diverse and have their own (unique) biological features.…”
Section: Introductionmentioning
confidence: 99%